New genus and species of silky lacewing (Insecta: Neuroptera: Psychopsidae) from the mid-Cretaceous Burmese amber - Lu, Xiumei; Zhang, Weiwei; Ohl, Michael; Liu, Xingyue (Zootaxa, 2017)
A new genus and species of the lacewing family Psychopsidae, Electropsychops handlirschi gen. et sp. nov., is described based on a well preserved male specimen from the mid-Cretaceous amber of Myanmar. The new genus possesses a number of diagnostic characters of Psychopsidae, i.e., the lack of a forewing median nygma, the presence of a vena triplica, and the straight and barely forked RA. However, it also exhibits some remarkable characters that are present in Osmylopsychopidae, such as the distally narrowed forewing costal space and the sigmoid MA stem in the hind wing. The relationship between Psychopsidae and Osmylopsychopidae is briefly discussed.